2001
DOI: 10.1093/glycob/11.6.505
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heparan sulfate oligosaccharides by nano-electrospray ionization mass spectrometry

Abstract: A highly sensitive method to identify and quantify heparan sulfate (HS) oligosaccharides by using nano-electrospray ionization mass spectrometry (nESI-MS) is described. The new approach allows us to detect approximately 50 nM of a chemically synthesized pentasaccharide with a structure of GlcNS6S-GlcA-GlcNS6S-IdoA2S-GlcNS6SOMe (3-OH pentasaccharide). Typically, solutions were infused for a total of 5 min, at an average flow rate of 30 nl/min, and the remaining sample was recovered from the nanovial. The spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…4A). We confirmed that the signals at m/z 648.8 and 486.4 contain sulfate groups by using neutral loss experiments as described in a prior publication (29). Briefly, the isolated ions were sequentially admitted to a collision cell filled with argon under controlled energy conditions, resulting in limited dissociation.…”
Section: Isolation Of the Gd-binding Octasaccharidesupporting
confidence: 55%
See 3 more Smart Citations
“…4A). We confirmed that the signals at m/z 648.8 and 486.4 contain sulfate groups by using neutral loss experiments as described in a prior publication (29). Briefly, the isolated ions were sequentially admitted to a collision cell filled with argon under controlled energy conditions, resulting in limited dissociation.…”
Section: Isolation Of the Gd-binding Octasaccharidesupporting
confidence: 55%
“…The MALDI-MS spectra were acquired in the linear mode using a Perseptive Biosystems Voyager Elite reflectron time-of-flight instrument fitted with a 337-nm laser as described elsewhere (28). The nESI-MS analysis was carried out using a Micromass Quattro II with QhQ geometry, a Z-spray source, and pulled borosilicate glass nanovials (29). In the neutral loss scan, MS/MS spectra were obtained by scanning Q1 and Q3 with an offset of 26.7 or 20 m/z in their scan cycles, corresponding to the loss of sulfate from the triple or quadruple charged octasaccharide, respectively (29).…”
Section: Analysis Of Hs Oligosaccharides Using Mass Spectrometry-twomentioning
confidence: 99%
See 2 more Smart Citations
“…(GlcUA-GlcNS3S6S) 5 -GlcUA-AnMan 145 Ϯ 24 10 (GlcUA-GlcNS6S) 5 -GlcUA-AnMan Ͼ100,000 Arixtra a GlcNS6S-GlcUA-GlcNS3S6S-IdoUA2S-GlcNS6S-OMe 33 Recomparin b Polysaccharide, no defined structure 57 a The 35 S-labeled Arixtra was prepared as described in a paper published previously (33). b The binding affinity of Recomparin to AT was taken from our previous publication (6).…”
Section: Substratesmentioning
confidence: 99%